Tuberculosis of the Breast: An Initial Presentation of the Metabolic Syndrome with Type 2 Diabetes Mellitus in a Young Nigerian Woman - M. A. Adeiza; R. Yusuf; A. A. Liman; P. Abur; F. Bello; A. A. Abba (Case Reports in Infectious Diseases)
Breast tuberculosis is an uncommon presentation of extra pulmonary tuberculosis. A 40-year-old obese woman presented with a right breast abscess which had failed to heal after surgical drainage. There was no family history of breast disease. Biopsy and histology of the lesion showed chronic granulomatous inflammation with positive stains for acid fast bacilli compatible with tuberculosis. Further evaluation confirmed metabolic syndrome with type 2 diabetes mellitus. She was placed on antituberculosis chemotherapy and appropriate therapy for diabetes mellitus with complete resolution of the lesion. We report this case because of its rarity and to highlight the association between tuberculosis an infectious disease and overnutrition in diabetes mellitus, a noncommunicable disease.